THE COMBINATION Of STAND-UP, HAND-UP, PAIR-UP(SUHUPU) AND THREE STEPS INTERVIEW STRATEGY TO IMPROVE STUDENTS’SPEAKING ABILITY at SMAN 1 BALAURING - Kie Samsia (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah IX Sulawesi, 2020)
The objective of this research was to find out whether or not combining SUHUPU and three steps interview strategy improve students’ speaking ability at the first grade students of SMAN 1 Balauring. This research used pre-experimental method which one class given pre-test, treatment, and post-test. The sampling technique used was purposive sampling technique. The total sample was 20 students. The result of the data indicated that there was a significant difference between pre-test and post-test, it was proved by the mean score of post-test was higher than the mean score of pre-test (11.30>13.05). The value of t-test was higher than t-table (20.261>2.093) at the level of significance 0.05 with the degree of freedom(df)=19. Based on the finding and discussion of the research, it can be concluded that by combining SUHUPU and three steps interview strategy can improve students’ speaking ability at the first grade students of SMAN 1Balauring.